Fetal heart rate variation after corticosteroids for fetal maturation. (September 2017) - Knaven, Olga; Ganzevoort, Wessel; de Boer, Marjon; Wolf, Hans
Abstract: Introduction: Several studies report a decrease of fetal heart rate (FHR) short-term variation (STV) after corticosteroids for improvement of fetal maturity and advice not to deliver a fetus for low STV within 2–3 days after corticosteroids. However, literature is not unanimous in this respect. This study intends to asses STV longitudinally after corticosteroid administration. Material and methods: A retrospective cohort study in a tertiary perinatal centre from 2009 to 2015 included all women who had been treated with corticosteroids at gestational age of 26–34 weeks, had a computerized cardiotocography (cCTG) before and after medication and did not deliver within 48 h. FHR and STV were stratified over 12-h periods and compared before and after corticosteroids. Women with imminent preterm labour (including PPROM) and women with placental problems (fetal growth restriction (FGR) or preeclampsia) (PE) were analysed separately. The effect of co-medication and gestational age was assessed. Results: The study included 406 women, 211 with imminent preterm labour, 195 with FGR-PE. After corticosteroids STV increased 1–2 ms (median 1.4; IQR 0.1–3.1) during the first 36 h after start of corticosteroids. Thereafter a small decrease of less than 1 ms (median −0, 6; IQR −1.6 to 0.3) compared to before CC was seen. Conclusions: The most conspicuous effect of corticosteroids is a short term increase of STV and decrease of FHR. A slight decrease after 48–71 h is possible, but abnormally low values should be considered as a sign of fetal distress. The clinical guidance, given by some, not to intervene because of a low STV after corticosteroids appears invalid.